A Retrospective Analysis of the Lauren Classification in the Choice of XELOX or SOX as an Adjuvant Chemotherapy for Gastric Cancer - Wang, Ke; Yu, Yuanyuan; Zhao, Jian; Meng, Qianhao; Xu, Chang; Ren, Jing; Zhang, Yanqiao; Wang, Yusheng; Wang, Guangyu (Current Gene Therapy, 2024)
Background: We aim to retrospectively explore the guiding value of the Lauren classification for patients who have undergone D2 gastrectomy to choose oxaliplatin plus capecitabine (XELOX) or oxaliplatin plus S-1 (SOX) as a further systemic treatment after the operation.Methods: We collected data of 406 patients with stage III gastric cancer(GC)after radical D2 resection and regularly received XELOX or SOX adjuvant treatment after surgery and followed them for at least five years. According to the Lauren classification, we separated patients out into intestinal type (IT) GC together with non-intestinal type(NIT) GC. According to the chemotherapy regimen, we separated patients into the SOX group together with the XELOX group.Results: Among non-intestinal type patients, the 3-year DFS rates in the SOX group and the XELOX group were 72.5%, respectively; 54.5% (P=0.037); The 5-year OS rates were 66.8% and 51.8% respectively (P=0.038), both of which were statistically significant.Conclusion: The patients of non-intestinal type GC may benefit from the SOX regimen. Differences were counted without being statistically significant with intestinal-type GC in the SOX or XELOX groups.
Keywords: gastric cancer